SOME CONSIDERATIONS ON THE INTANGIBLE CULTURAL HERITAGE OF KARAKALPAKSTAN (Scientific journal of the Fergana State University, 2026)
This article examines jewelry art, the national women's headdress "saukele" and the wedding dress "kyzyl kiymeshek", which are considered unique elements of the intangible cultural heritage of the Karakalpaks. In particular, the history, classification and comparative analysis of these elements are scientifically covered.